Teori Belajar Behaviorisme Ivan Pavlov dan Implikasinya dalam Pembelajaran Bahasa Arab Siswa Madrasah Tsanawiyah Negeri - Ariane Nafila; Dewi Utami; Dadan Mardani (Departement of Mathematics Education, 2023)
This study aims to find out the implications of Ivan Pavlov's behaviorism learning theory in learning Arabic for class VIII students of Madrasah Tsanawiyah Negeri (MTsN) Sukabumi City and its advantages and disadvantages. The method used in this study is a qualitative approach with observation techniques. This study also used interview techniques for Arabic teacher in class VIII MTs Negeri Sukabumi City and to 12 students of MTs Negeri Kota Sukabumi who came from the 4 classes. The results showed that there are many behaviors in Arabic language learning for class VIII MTs Negeri Sukabumi City students that are relevant to Ivan Pavlov's concept of behaviorism learning theory, namely to make students learn, teacher provides certain conditions. The advantage of this learning theory is suitable to be applied to Arabic language learning for class VIII students of MTs Negeri Sukabumi City, because most of the students show the expected response when the teacher often applies repetition and habituation related to the material being studied. The disadvantage lies in the hours of study that affect the response given by the students. Students who learn Arabic in the morning tend to be quick in responding to the stimulus provided by the teacher.